Management Learning as Collaborative Visual Encounter: Learning Lessons From Research and Practice. (December 2016) - Robson, Ian
This article reviews a body of literature that relates to the use of aesthetic, specifically visual, methods in organizational research and management education. Visual methods are associated with a range of benefits for those studying management and organization, including the elicitation of emotional responses, support for reflection and self-reflexivity, making varied forms of knowledge explicit, and in supporting dialogue and collaborative learning. Key implications for management educators are outlined, which include the need to appreciate the nature of aesthetic-visual "knowing" and to evaluate methods with pedagogical criteria, to consider the type of visual "space" educators need to create, to build individuals' capacities to use visual methods, and to facilitate visual encounters appropriately. A set of practical "starting points" are also identified for management educators, drawn from the author's teaching practice.